2006
DOI: 10.5089/9781451864830.001
|View full text |Cite
|
Sign up to set email alerts
|

Default, Credit Growth, and Asset Prices

Abstract: This Working Paper should not be reported as representing the views of the IMF.The views expressed in this Working Paper are those of the author(s) and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author(s) and are published to elicit comments and to further debate. This paper uses a Merton-type estimate of the probability of default (PoD) for the main banks in a sample of Organization for Economic Cooperation and Development and middle-income… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Miller et al (2011) found that the impact of the 'collateral' channel is stronger than 'wealth' effects in the US. 12 Although the causality between credit and housing prices goes in both directions, the strongest effect is the one that emerges from housing prices to credit (Hofman, 2003;Goodhart et al, 2006). 13 The effect of disposable income on credit is uncertain (Nobili and Zollino, 2012).…”
mentioning
confidence: 99%
“…Miller et al (2011) found that the impact of the 'collateral' channel is stronger than 'wealth' effects in the US. 12 Although the causality between credit and housing prices goes in both directions, the strongest effect is the one that emerges from housing prices to credit (Hofman, 2003;Goodhart et al, 2006). 13 The effect of disposable income on credit is uncertain (Nobili and Zollino, 2012).…”
mentioning
confidence: 99%
“…He finds that property prices are an important determinant of the long-term trend development in credit over this period and that increases in property prices have a highly significant positive effect on credit dynamics. 8 Hofmann (2003), Goodhart and Hofmann (2004a) and Goodhart et al (2006) analyse the relationship between bank lending and property prices based on a multivariate empirical framework and find that causality does in fact seem to go in both directions, but that the effect of property prices on credit appears to be stronger than the effect of credit on property prices. Gerlach and Peng (2005) analyse the link between property prices and credit in Hong Kong and find that causality runs from property prices to lending, rather than conversely.…”
mentioning
confidence: 99%
“…It simply means that banks start 'selling the loans'. Borio et al (2001), Davis and Zhu (2004), and Goodhart et al (2005) state that the rapid growth of indebtedness follows the rapid growth of the price level of the real estate market. It makes possible the acquisition of new financing more widely available.…”
Section: Literature Reviewmentioning
confidence: 97%